Legal Regulation of the Emerald Network: National and Global Aspects - Bevz, Olena (Journal of Vasyl Stefanyk Precarpathian National University, 2018)
The article is devoted to the definition of the legal nature of the Emerald network, as well as to the issues of the formation of the Emerald Network in the context of Ukraine's international obligations. In particular, the history of the appearance of the term “Emerald Network” in international acts, the criteria and the procedure for designating territories of the Emerald Network is investigated. In addition, the article deals with the problems connected with the legal provision of the formation of the Emerald Network in Ukraine. It is emphasized that the adoption of the relevant legislation is foreseen by the international obligations of Ukraine as a Member State of Convention on the Conservation of European Wildlife and Natural Habitats and Association Agreement between the European Union and its Member States, of the one part, and Ukraine, of the other part. The provisions of the draft Law of Ukraine "On the Territories of the Emerald Network” are analyzed.